Novel Soloxolone Amides as Potent Anti-Glioblastoma Candidates: Design, Synthesis, In Silico Analysis and Biological Activities In Vitro and In Vivo - Andrey V. Markov; Anna A. Ilyina; Oksana V. Salomatina; Aleksandra V. Sen'kova; Alina A. Okhina; Artem D. Rogachev; Nariman F. Salakhutdinov; Marina A. Zenkova (MDPI AG, 2022)
The modification of natural or semisynthetic triterpenoids with amines can be explored as a promising strategy for improving their pharmacological properties. Here, we report the design and synthesis of 11 novel amide derivatives of soloxolone methyl (SM), a cyano enone-bearing derivative of 18βH-glycyrrhetinic acid. Analysis of their bioactivities in vitro and in silico revealed their high toxicity against a panel of tumor cells (average IC50(24h) = 3.7 µM) and showed that the formation of amide moieties at the C-30 position of soloxolone did not enhance the cytotoxicity of derivatives toward tumor cells compared to SM, though it can impart an ability to pass across the blood-brain barrier. Further HPLC-MS/MS and mechanistic studies verified significant brain accumulation of hit compound 12 (soloxolone tryptamide) in a murine model and showed its high anti-glioblastoma potential. It was found that 12 induced ROS-dependent and autophagy-independent death of U87 and U118 glioblastoma cells via mitochondrial apoptosis and effectively blocked their clonogenicity, motility and capacity to form vessel-like structures. Further in vivo study demonstrated that intraperitoneal injection of 12 at a dosage of 20 mg/kg effectively inhibited the growth of U87 glioblastoma in a mouse xenograft model, reducing the proliferative potential of the tumor and leading to a depletion of collagen content and normalization of blood vessels in tumor tissue. The obtained results clearly demonstrate that 12 can be considered as a promising leading compound for drug development in glioblastoma treatment.